Analisis Penerapan PSAK 69 Agrikultur atas Aset Biologis untuk Tata Kelola Keuangan Pada PT. Indah Bumi Plantasi - Damayanti, Fitri; Nurodin, Idang; Indrawan, Andri (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to find out the description of the application of PSAK 69 related to biological assets in PT. Indah Bumi Plantasi for financial governance. This research uses descriptive qualitative method. Sources of data obtained by means of observation, interviews, and documentation. To analyze biological assets based on PSAK 69, 3 valuation methods are used, namely recognition of biological assets, measurement of biological assets, and disclosure of biological assets. The results of this study indicate that PT. Indah Bumi Plantasi disclosed and acknowledged its biological assets in the form of teak trees which had shrunk to 3 (three) types of trees according to the type and age of the tree, namely New Plants (TB), Immature Plants (TBM), and Mature Plants (TTM). Biological assets at PT. Indah Bumi Plantation is measured using fair value/market price to make it easier to get profits. This shows that PT. Indah Bumi Plantasi has not fully implemented PSAK 69, because there are still aspects that are not in accordance with PSAK 69 and employees who are still mistaken about PSAK 69.